Robust image watermarking based on Dual Intermediate Significant Bit (DISB) - Mohammed, Ghassan N.; Yasin, Azman; Zeki, Akram M. (2014)
The most important requirements should be available on any watermarking systems which are the robustness against possible attacks and the quality of the watermarked images. In most applications, the watermarking algorithm embeds the watermark have to be robust against possible attacks and keep the quality of the host media as possible. The relationship between the two requirements is completely conflict. In this study, the method focuses on the robustness against chosen attacks for the watermarked image based on Dual Intermediate Significant Bit (DISB) model. This method requires embedding two bits into every pixel of the original image, while and the other six bits are changed so as to directly assimilate the original pixel. In the case, when the two hidden bits are equal or not equal to the original bits, there is a need to use mathematical equations to solve this problem which derived and applied in this study. The results show that the proposed model produces robustness watermarked images as compared to our previous method when focuses on the high quality of the watermarked image which proved that proposed method is better as compared with the Least Significant Bit (LSB) after embedding two bits. The best values investigated when the Peak Signal to Noise Ratio (PSNR) is equal or more than 30db, and finding the best Normalized Cross Correlation (NCC) to evaluate the image resistance against attacks. The best values investigated when the two embedded bits are k1=4 and k2=6.